HEPATITIS C: NEW PERSPECTIVES IN TREATMENT AND THE ROLE OF PHARMACEUTICAL ASSISTANCE (REMUNOM, 2025)
Hepatitis C is an infectious disease caused by the Hepatitis C Virus (HCV), which belongs to the Flaviviridae family, of the Hepacivirus genus, which affects around 3% of the world's population. Currently, with a vast therapeutic arsenal for the treatment of hepatitis C, the class of medications known as second-generation Direct Action Antivirals (DAAs) is used. The research aims to address the role of pharmaceutical assistance in new perspectives regarding the treatment of hepatitis C. To this end, a bibliographical review of the literature was carried out consisting of the narrative type, based on publications of scientific articles available on database websites. Virtual services, such as: NLM/PubMed, Lilacs and SciELO in the period between 2019 and 2023. It was then noted that the entry of Pharmaceutical Assistance in the treatment of Hepatitis C promotes better adherence to treatment, promoting direct beneficial effects to the patient. Therefore, it is concluded that the pharmacist plays a central role in the safety and effectiveness of the use of medicines, seeking to optimize health-related results and through personalized guidance is able to identify and prevent possible risks and adverse reactions associated with the use of medicines, aiming for rational use.